Strategi Pengembangan Manajemen di Ngasinan Fashion Kediri - Febriyanti, Lina; Muliawati, Niken Ayu (Aktualisasi Pengabdian Masyarakat, 2023)
One of the business opportunities that most entrepreneurs are interested in is the fashion business, because fashion is considered a major requirement in today's society in various circles. The Ngasinan Fashion store is one of the shops engaged in the clothing trade located in Rejomulyo, Kediri City, which has been running its business since 2014 until now, it still exists and even has a branch located not far from the first shop in Blabak, Kediri Regency. This research will discuss what problems often arise in the shopping sector. The research method used in this research is qualitative research where the data collection model used in this field research is in the form of observations and interviews, to obtain data, phenomena, or events being studied. The results of the research show that there are several problems that often arise, starting from the shop owner's lack of fluency in the latest technology and innovations, lack of observance in seeing developments in trends in society, product defects from distributors, lack of cooperation between employees, and shops that are empty of visitors during the day. usual, and only crowded at certain times such as during holidays. This research also discusses the solutions that have been applied to the Ngasinan fashion shop so that the problems that arise can be handled properly.